Performance Evaluation of MIMO/STBC Systems with Antenna Selection Techniques Working Under Nakagami-m Fading Channels - Shyamveer (My University, 2011)
The latest wireless communication techniques such as high speed wireless internet application demand higher data rates and better quality of service. However, “Multipleinput multiple-output (MIMO) systems can increase the system capacity and improve transmission reliability. By transmitting multiple copies of data, a MIMO system can effectively combat the effects of fading. Moreover, using MIMO system will lead to increase of system cost and complexity, which constrain the development of MIMO technology, however, the antenna selection (AS) techniques have been applied in MIMO system design to reduce the system efficiently reduce the complexity and cost. There are three possible AS scheme namely receive antenna selection (RAS), transmit antenna selection (TAS) and joint antenna selection (T-RAS). Thus, this thesis presents a comprehensive analysis of antenna selection in MIMO/STBC system over Nakagami-m fading channel. The main work is as following: We briefly explain and analyze performance all three possible antenna selection ( TAS, RAS, T-RAS ) scheme in MIMO/STBC system and drive the BER expression in close-form, where system select an antenna ( at transmitter, receiver or both side ) that maximizes the received signal power. This thesis also compares the performance of all three possible antenna selection schemes. Exact bit error rate (BER) expression for binary phase shift keying (BPSK) modulations are derived by using the moment generating function (MGF)-based analysis method of the output signal-to-noise ratios (SNR). The Nakagami-m distribution has been considered for MIMO channel modeling since a wide range of fading channels, from severe to moderate, can be modeled by using Nakagami-m distribution. The Rayleigh distribution is a special case of the Nakagami-m distribution. In this thesis, we analyze the error performance RAS, TAS & T-RAS of MIMO/STBC schemes over Nakagami-m fading channels. Our approach can be used over not only independent but also arbitrary correlated Rayleigh, Nakagami-m and Rician fading channels. Key words: - Multiple input multiple output (MIMO), space time block code (STBC), Moment generating function (MGF), Nakagami-m fading, transmit antenna selection (TAS), receive antenna selection (RAS), joint transmit and receive antenna selection (T-RAS), Binary Phase-Shift Keying (BPSK), bit error rate (BER), symbol error rate (SER),signal to noise ratio (SNR)
M.E.
Keywords: MIMO(Multiple input multiple output); AN(Antenna selection)